2007
DOI: 10.1002/rra.1033
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of primary and heterotrophic productivity in an arid lowland river

Abstract: Three river conceptual models make differing predictions about the major source of primary production in lowland rivers, acknowledging the importance of primary productivity in the ecology and management of lowland rivers. Patterns of primary production in lowland rivers are still an area of considerable uncertainty. The objective of this study was to examine the major sources and transformations of organic matter in an Australian lowland river and compare them to the predictions of existing models. The broad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 68 publications
(80 reference statements)
2
32
0
Order By: Relevance
“…Nevertheless, there was also a downstream trend of increasing chlorophyll-a concentrations from LR1 to LR4. This finding is consistent with predictions of water column productivity in riverine systems, with water column productivity and biomass highest in the lower and slower flowing sections of rivers than in the more upstream reaches (Thorp and Delong, 1994;Gawne et al, 2007). In the Logan River, high enzyme activity levels were observed at all sites for both the enzymes responsible for decomposing carbohydrates and those involved in obtaining phosphate.…”
Section: Logan Riversupporting
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, there was also a downstream trend of increasing chlorophyll-a concentrations from LR1 to LR4. This finding is consistent with predictions of water column productivity in riverine systems, with water column productivity and biomass highest in the lower and slower flowing sections of rivers than in the more upstream reaches (Thorp and Delong, 1994;Gawne et al, 2007). In the Logan River, high enzyme activity levels were observed at all sites for both the enzymes responsible for decomposing carbohydrates and those involved in obtaining phosphate.…”
Section: Logan Riversupporting
confidence: 90%
“…Longitudinal trends in the source, concentration and composition of carbon and nutrient pools, and how they influence river function, represent an important yet often overlooked component of river management and understanding (Gawne et al, 2007). This is despite the fact that longitudinal connectivity and transport of both nutrients and carbon within river systems have received considerable conceptual attention.…”
Section: Introductionmentioning
confidence: 97%
“…Understanding longitudinal variation in the contributions of different energy sources to river food webs is important for both ecological theory and river management (Gawne et al 2007). The River Continuum Concept of Vannote et al (1980) suggests that the dominant food resources for primary consumers vary in a predictable manner from headwater streams to large rivers.…”
Section: Introductionmentioning
confidence: 99%
“…Given the hydrological variability, it has been hypothesised that floodplain-derived carbon is an important source of energy for aquatic food webs; however, regulation has limited the contribution of floodplain-derived carbon (Gawne et al 2007;Robertson et al 1999). Recent studies have found that autochthonous carbon plays a more significant role than predicted in riverine primary productivity (Oliver and Merrick 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the regionally significant Murrumbidgee River, Vink et al (2005) found that the ecosystem was predominantly heterotrophic during a period of in-channel flow but there was a trend of increasing autotrophic activity downstream. Additionally, Gawne et al (2007) found that both heterotrophic and autotrophic productivity were significant contributors to the productivity of the Murray River but that this varied seasonally. These studies have largely taken place under extended low-flow conditions (Bond, Lake et al 2008); however, recent floods in New South Wales, Australia, provided the opportunity to assess carbon dynamics under both low and high flows.…”
Section: Introductionmentioning
confidence: 99%